(untitled) (Scholars’ Journal, 2022)
Factors Affecting School Participation of Visually impaired children is a narrative inquiry on the affecting factors that hinders the visually impaired children at school and home from learning. This research aims at exploring the current scenario of the participation of visual impaired children in school education and its affecting factors. I used qualitative research design with a narrative approach. The site of this study was one of the community schools in the Parsa district. The population of this research was two students and a teacher from the school. I used a purposive sampling procedure. I conducted an in-depth interview using interview guidelines as a data collection tool, developed themes based on the information provided by the participants, and linked them with theories. It was found that the participation of visually impaired children seemed very poor being affected by the factors like-poverty, pedagogical preparation, required materials for visually impaired children, peer behavior, lack of self-efficacy, decreased ability to perform physical tasks, traditional perceptions towards disability, violence and defending capability. This research will support the policymakers, teachers, related stakeholders, and duty bearers for policy making and implementation to increase the participation of visual impairment students in school education and reduce the factors that influence them to place them in educational opportunities.